2006
DOI: 10.1002/rcs.71
|View full text |Cite
|
Sign up to set email alerts
|

Short-term impact of a robot-assisted laparoscopic prostatectomy ‘mini-residency’ experience on postgraduate urologists' practice patterns

Abstract: A 5 day intensive RALP M-R course seems to encourage postgraduate urologists, already familiar with laparoscopy, to successfully incorporate robotic surgery into their practice. The take rate, or the percentage of participants performing robotic-assisted surgery within 14 months after M-R, was 95%. Continued follow-up will ultimately determine the long-term effectiveness of this 1 week intensive training programme for postgraduate urologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 10 publications
1
42
0
Order By: Relevance
“…Cadaveric setting is used for robot-assisted surgery, laparoscopic, urologic surgery and minimally invasive stone surgery as well. [8,12,13] Vlaovic et al [13] showed that a week long intensive laparoscopic and robotic urologic surgery training improves test scores significantly. McDougall et al [12] reported that a five days of robotic training course which includes cadaveric training encourages the experienced laparoscopic urologists to incorporate robotic surgery into their practice.…”
Section: Fresh Frozen Cadaveric Model In Laparoscopic Training In Surmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadaveric setting is used for robot-assisted surgery, laparoscopic, urologic surgery and minimally invasive stone surgery as well. [8,12,13] Vlaovic et al [13] showed that a week long intensive laparoscopic and robotic urologic surgery training improves test scores significantly. McDougall et al [12] reported that a five days of robotic training course which includes cadaveric training encourages the experienced laparoscopic urologists to incorporate robotic surgery into their practice.…”
Section: Fresh Frozen Cadaveric Model In Laparoscopic Training In Surmentioning
confidence: 99%
“…[8,12,13] Vlaovic et al [13] showed that a week long intensive laparoscopic and robotic urologic surgery training improves test scores significantly. McDougall et al [12] reported that a five days of robotic training course which includes cadaveric training encourages the experienced laparoscopic urologists to incorporate robotic surgery into their practice. The efficiency of cadaver-based training has been demonstrated in obstetrics and gynecology as well.…”
Section: Fresh Frozen Cadaveric Model In Laparoscopic Training In Surmentioning
confidence: 99%
“…Similarly, a questionnaire was sent to the initial 21 participants in the robot-assisted laparoscopic prostatectomy M-R 1 to 14 months (mean, 7.2) later. 6 The response rate to this questionnaire was also 100%. Most (80%) of the participants had prior laparoscopic training in their urology residency, and 25% were performing robotassisted laparoscopic prostatectomy before their M-R. After their M-R, 95% of the participants were performing robot-assisted laparoscopic prostatectomy.…”
Section: Discussionmentioning
confidence: 91%
“…8 The overall 85% success or "take" rate of the University of California, Irvine M-R program compares favorably to the 83% take rate of this time-intensive laparoscopic proctoring training program. 5,6 Of course, further long-term follow-up of both courses is necessary to determine the durability of these learned skills.…”
Section: Discussionmentioning
confidence: 99%
“…At the University of California Irvine, the shortand long-term benefits of procedure-specific 5-day robotic surgery training courses have been reported. 14,15 More recently, educators at the University of Texas Southwestern have published feasibility, validity, and reliability data on a competency-based inanimate training program for robotic surgery, which also addresses the need for structured training programs. 16 Surgical training literature has clearly demonstrated the superior educational outcomes associated with curricula that adhere to the principles of spaced-learning and competency-based training.…”
Section: Discussionmentioning
confidence: 99%